Measuring health : a guide to rating scales and questionnaires - McDowell, Ian, 1947- (New York ; Oxford : Oxford University Press, 2006)
This text provides reviews of the quality of over 100 health measurement instruments. It guides the reader in choosing among rival methods, showing how to administer and score them. It also includes a historical and technical introduction to the field of health measurement.
Previous ed.: 1996.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Health surveys; Social surveys; Health status indicators -- Measurement